Modeling Revisit Intention in Coastal Ecotourism: A Conceptual Framework from the Case of Beach Tourism in Bangka Belitung - Fitriani, Yulia; Suhud, Usep; Wibowo, Setyo Ferry (Siber International Journal of Digital Business (SIJDB), 2025)
Coastal ecotourism serves as a key strategy in the development of sustainable tourism, particularly in archipelagic regions such as Bangka Belitung. Despite possessing internationally recognized natural wealth through its designation as a UNESCO Global Geopark, the region continues to experience a relatively low level of tourists’ revisit intention. This study aims to develop a conceptual framework that explains revisit intention by positioning perceived ecotourism value as a mediating variable. The proposed model integrates three core constructs green consumption behavior, digital tourism behavior, and coastal ecotourism experience drawing from interdisciplinary perspectives across tourism, sustainability, and digitalized tourist behavior literature. A synthesis of existing literature reveals that tourists with environmentally conscious lifestyles and active digital engagement tend to perceive greater value in their travel experiences. This perceived value encompassing functional, emotional, and social dimensions plays a significant role in reinforcing their intention to revisit a destination. The framework aligns with the Value-Based Adoption Model (VAM) and the Theory of Planned Behavior (TPB), both of which emphasize psychological and behavioral determinants in shaping loyalty toward sustainable destinations. Strategically, the model provides practical guidance for destination managers in designing high-value tourist experiences through the synergy of ecological conservation and digital integration. Further empirical validation is required to test the model across diverse coastal tourism contexts, particularly in efforts toward post pandemic recovery.